A Mimo Radar for Vital Signs Recording - Sacco, G.; Pisa, S. (Progress in Electromagnetics Research Symposium, 2019)
The proposed work presents a Frequency Modulated Continuous Wave (FMCW) radar operating at 5.8 GHz based on the Multiple Input Multiple Output (MIMO) technique. This solution allows not only to evaluate the target position, but also to achieve an imaging of the investigated environment. The vital signs measurement has been done instead with a phase-based algorithm. The radar has been realised with integrated components together with an asymmetric power divider, a filtering and amplifying stage and microstrip antennas ad-hoc designed. The imaging and the breath algorithms have been tested together with the antennas and the filtering stage showing performances suitable for the proposed application.